2020
DOI: 10.1038/s41598-020-66467-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics and Spatiotemporal Analysis of Acute Hemorrhagic Conjunctivitis from 2004 to 2018 in Chongqing, China

Abstract: Chongqing is one of the five provinces in China that has the highest incidence of acute hemorrhagic conjunctivitis (AHC). Data of AHC cases from 2004 to 2018 were obtained from National Notifiable Diseases Reporting Information System (NNDRIS). Descriptive statistical methods were used to analyze the epidemiological characteristics; incidence maps were used to reflect incidence trends in each district; spatial autocorrelation was used to identify hotspot regions and spatiotemporal patterns of AHC outbreaks; sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…It seems likely that the periodicity of the curves is caused by a seasonal effect since the timing of the highest search rates through the analyzed 4 years was very similar in the 13 curves ( Figure 1 ). Seasonality is well known for infectious conjunctivitis [ 18 ]. This seasonality is also observable in the density plot for the patients diagnosed with conjunctivitis (ICD codes in the “H10.-” code group) in the centralized ophthalmologic emergency practice for the Freiburg region ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that the periodicity of the curves is caused by a seasonal effect since the timing of the highest search rates through the analyzed 4 years was very similar in the 13 curves ( Figure 1 ). Seasonality is well known for infectious conjunctivitis [ 18 ]. This seasonality is also observable in the density plot for the patients diagnosed with conjunctivitis (ICD codes in the “H10.-” code group) in the centralized ophthalmologic emergency practice for the Freiburg region ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The LISA map was divided into four spatial cluster patterns, namely high-high, low-low, high-low and low-high. 18 19 High-high patterns indicated that areas with a high incidence of pertussis were surrounded by areas with a high incidence of pertussis. Low-low patterns indicated that areas with a low incidence of pertussis were surrounded by areas with a low incidence of pertussis.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, this is the first work to directly investigate the oscillatory properties of the nine class C infectious diseases together in mainland China. Previous studies mostly targeted one specific disease [Influenza (55), Mumps (56)(57)(58)(59)(60), Rubella (61)(62)(63), AHC (64)(65)(66)(67)(68), Leprosy (69-72), Typhus (73)(74)(75)(76), Leishmaniasis (77,78), Hydatid disease (79-81), HFMD (82)(83)(84)(85)(86)], more in a statistical description sense on the numbers, ratios, or dissecting multiple components to fit the data. These studies seldom investigated these diseases directly from the oscillatory view, but we focused more on the ubiquitous oscillatory property of these class C diseases together to find some common laws as a whole.…”
Section: Comparison With Previous Workmentioning
confidence: 99%